ELEMENTS OF POSTMODERNISM IN UZBEK PROSE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study explores the elements of postmodernism in Uzbek prose, focusing on how contemporary Uzbek writers reinterpret narrative form, meaning, and literary structure in the context of global postmodern thought. Postmodernism, as a literary and cultural movement, challenges fixed meanings, linear storytelling, and the authority of a single narrative voice. In Uzbek prose, these tendencies have become more visible particularly after the independence period, when writers began to experiment with new artistic forms and narrative strategies. The research highlights several key postmodern features in Uzbek prose, including fragmentation of narrative structure, intertextuality, metafictional techniques, and the use of ambiguity and irony. These elements demonstrate a shift from traditional realist storytelling toward more open-ended and interpretative forms of writing. The study also shows that Uzbek postmodern prose often blends local cultural traditions, such as folklore and historical memory, with global literary influences, creating a hybrid narrative space.